The improvement effect of insoluble dietary fiber of Polygonatum sibiricum on hyperlipidemia in high-fat diet mice via gut microbiota and metabolites - Ma, Yanli; Ke, Jingxuan; Wang, Yuan; Zhou, Yuhui; Gao, Xinyu; Wang, Xin; Shen, Qingshan (Frontiers in Nutrition, 2025)
ObjectivePolygonatum sibiricum is rich in insoluble dietary fiber (IDF), but its antihyperlipidemic effect remains unclear. This study investigated the antihyperlipidemic effect of Polygonatum sibiricum’s IDF (PIDF) in high-fat diet mice.MethodsMale C57BL/6 J mice were fed with a high-fat diet continuously for 8 weeks. At the same time, the low-dose and high-dose groups were supplemented with 0.5 g/kg·BW and 1.0 g/kg·BW of PIDF, respectively. The weight and food intake of the mice were measured during the experiment. After 8 weeks of feeding, the organ weight, serum indexes, and liver function were investigated. Furthermore, the mechanism of antihyperlipidemic was explained by analyzing the gut microbiota and metabolites.ResultsThe results of the LIDF and HIDF showed that the PIDF treatment significantly alleviated the liver and kidney weight and body fat index. PIDF administration remarkably increased the high-density lipoprotein cholesterol level and enhanced hepatic superoxide dismutase activity in high-fat diet-fed mice. The levels of total cholesterol, triglycerides, low-density lipoprotein cholesterol, glucose, and aspartate transaminase in the HIDF were significantly lower than in the high-fat diet group. In addition, PIDF supplements also decreased the ratio of Bacillota to Bacteroidota, increasing the relative abundance of Alistipes and Akkermansia. Furthermore, metabolites suggest that dietary increases in PIDF can promote lipid and amino acid metabolism. Hence, PIDF improves lipid metabolism by regulating the gut microbiome and influencing host metabolism.ConclusionIt can be concluded that PIDF may alleviate hyperlipidemia by regulating cholesterol metabolism, increasing the abundance of beneficial microorganisms, and controlling its metabolites. The results of this study accelerated the application of PIDF in the health food industry.